KEBIJAKANRUANG TERBUKA HIJAU DALAM MENANGGULANGI POLUSI UDARA DI KABUPATEN BANTUL, YOGYAKARTA - Hayati Akhbar Saingura; Eko Priyo Purnomo (Jurnal Kesehatan Masyarakat dan Lingkungan Hidup, 2020)
The growth of an area at this time is happening very rapidly, both in the sector of population mobilization and urbanization and infrastructure. This growth brings a good impact to support the economy, but also has a bad impact on the surrounding environment such as air pollution. To minimize air pollution by implementing Green Open Space (RTH) policies regulated in Law Number 26 Year 2007 regarding Spatial Planning which states an urban area is required to have a minimum of 30% Green Open Space (RTH) of its area. . But in reality, it is difficult to realize and fulfill 30% of urban areas into Green Open Space (RTH). Like Kab. Bantul Green Open Space (RTH) is currently still at 13.65%, even though it has been regulated in a Regional Regulation since 1992. Then in Kab. Bantul by doing intensive and exnsive forms of activities.